Status of referral to physiotherapy among hiv positive patients at Chris Hani Baragwaneth hospital johannesburg South Africa 2005 - H. Myezwa; A. Stewart; N. Mbambo; P. Nesara (AOSIS, 2007)
HIV continues to be a major health problem in South Africa. The multiple diagnoses that the disease presents with, needs a holistic and comprehensive management approach. Physiotherapy and rehabilitation play a role in this management approach. Understanding the full scope of conditions that are present and those that are suitable for physiotherapy intervention is an essential prerequisite to developing appropriate curricula, intervention models or systems. It is accepted that HIV rehabilitation interventions are based largely on functional deficits ( O'Dell  1996), however  in South Africa functional deficits have not been fully explored. A common starting point, with the medical model of management was considered to be at the diagnosis level as this information would be more readily available than functional deficits. Purpose: This study aimed to establish how much and in which aeitiology is physiotherapy involved in the management of HIV within an inpatient hospital setting at Chris Hani Baragwaneth Hospital. This minor study forms part of a larger study establishing physiotherapy curricula needs. Method: Aretrospective review of patient records was carried out in order to identify conditions suitable for physiotherapy and to determine the referral patterns to physiotherapy. Findings: Of the 732 records reviewed and used in the study, 47% (n=344) of the patients were HIV positive. From these records, 19% (n=139) had diagnoses considered suitable for physiotherapy and only 2% (n=3) of these 139 patients were referred to physiotherapy. Conclusion: Almost half of the patients in the medical units were HIV positive. Although the referral rate was very low, some of these patients presented with diagnosis that are traditionally seen by physiotherapists.  None of the patients' records indicated examination of the patients' physical status such as exercise tolerance, mobility, muscle strength, lung function or pain. This study is by no means fully representative of the full scope of the epidemiology of conditions that can be seen by physiotherapists or their referral status but does give some indication of what conditions are, and could potentially interface with physiotherapy.